ضمانات المستهلك بعد ابرام عقد البيع بالتقسيط دراسة تحليلية مقارنة - حسين, أ. م. د.زبير مصطفى; عمر, م.افيستا سالار (Sulaimani Journal for Humanities, 2023)
The need of consumers for goods and services prompts them to contract with professionals in a haste, in order to obtain what they need for their urgent needs. Given the growing elements of consumer vulnerability as a result of industrial development and technological progress that led to a discernible change in the methods of producing goods and services as well as methods of distribution and marketing. As the professionals start to conduct thier business through large organizations with both the financial and informational resources to do so, it is now simpler for him or her to employ a variety of contemporary methods of promotion and publicity, such as advertisements that may contain inaccurate or misleading information. In addition, the process of modifying them through sample contracts that contain clauses, the majority of them are in the professional's favour. Due to the latter's dominance in terms of economy, law, cognition, and technology, there is an unequal relationship in the contract between the consumers of goods and services and their providers. light of these facts, recent developments, and the limitations of the basic rules governing the contract provisions in civil legislation, it has become important to establish legal guidelines for consumer protection in instalment sales contracts. The purpose of this study was to demonstrate consumer protection techniques in instalment sales by giving the consumer the right to cancel the instalment sale contract that he or she had previously entered into with the professional or professional, as well as through other agreement guarantees that are included in the contract that is concluded between them. Through this research, we tried to determine the extent of protection provided by general rules and special legislation to the consumer after the conclusion of the contract. We concluded that the Iraqi legislator allowed the consumer to withdraw from the contract according to certain conditions and without obligating him or her to a specific period. Besides, the consumer bears the expenses of returning in the event that he or she uses the right to return unless the trader provided a commodity or service that is not stipulated in the contract, but has an equivalent quality and price, so the consumer is notified of that, and every condition that limits or restricts the consumer's right to return is invalidated. Likewise, the Iraqi legislator regulated some forms of enticing guarantees provided by the trader in the Consumer Protection Law in Article (6) Paragraph (First / D) regarding commodities whose nature requires that, such as a guarantee for the period that is agreed upon with the supplier without incurring additional expenses. And, the sixth paragraph from the same article that gave the consumer the right to obtain after-sales services according to an agreement concluded with the supplier, which may regulate these texts in the case of enticing maintenance. As we find that the Iraqi legislator was successful in organizing this issue. We suggested to the Iraqi legislator to specify the period during which the consumer is allowed to withdraw from the contract within fifteen days from the date of his receipt of the subject matter of the contract, without leaving that to jurisprudence and the judicial opinion. In addition to regulating the guarantees granted to the consumer in the period after the conclusion of the contract fully and clearly in the consumer protection law.